STRATEGIC DIVERSIFICATION OF EUROBOND ISSUANCE BY UZBEK CORPORATE ISSUERS: CURRENCY, INSTRUMENT TYPES, AND INVESTOR BASE EXPANSION (E Global Congress, 2026)
Uzbekistan’s integration into international capital markets has accelerated significantly over the past several years, driven by the country’s inaugural sovereign Eurobond issuance, ongoing economic reforms, and increasing investor confidence in its long-term development trajectory. The sovereign Eurobond of 2019 established a liquid benchmark yield curve and served as a catalyst for corporate and quasi-sovereign issuers, enabling them to pursue global funding opportunities with greater visibility and pricing efficiency. This shift coincides with a broader policy agenda aimed at market liberalization, modernization of the banking sector, and the gradual transition toward market-based financing models.